1999
DOI: 10.1007/s100480050081
|View full text |Cite
|
Sign up to set email alerts
|

Potential treatment of transthyretin-type amyloidoses by sulfite

Abstract: Familial amyloidotic polyneuropathy (FAP) and senile systemic amyloidosis (SSA) are characterized by systemic extracellular deposition of insoluble transthyretin (TTR) fibrils. While only normal TTR is found in fibrils from SSA patients who predominantly suffer from cardiomyopathy, autosomal dominant FAP preferentially affects peripheral nerves and heart and is associated with so-called amyloidogenic mutations of this protein, giving rise to TTR forms of decreased stability. Using isoelectric focusing in urea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 0 publications
2
39
0
1
Order By: Relevance
“…4A) is quite similar with that of monomers with cysteinylated Cys10 [6]. Monomers with S-sulfonated Cys10 [16] or reduced Cys10 (after reaction with DTT) [6] are more stable. From these observations we conclude that the dimer conformational stability near neutral pH levels corresponds with monomer and tetramer conformational stability observed by IEF under partial denaturing conditions in the range of pH 5-5.7.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…4A) is quite similar with that of monomers with cysteinylated Cys10 [6]. Monomers with S-sulfonated Cys10 [16] or reduced Cys10 (after reaction with DTT) [6] are more stable. From these observations we conclude that the dimer conformational stability near neutral pH levels corresponds with monomer and tetramer conformational stability observed by IEF under partial denaturing conditions in the range of pH 5-5.7.…”
Section: Resultssupporting
confidence: 53%
“…2. We have demonstrated earlier that there is significant variability of the conformational monomer stability depending on differential ligands bound at Cys10-SH of the TTR monomer [6], that the ATTR-V30M mutation is a potent destabilizer of the folded monomeric structure [16], and that the genetic and nongenetic effects are additive. A sample from a heterozygote for normal TTR (N) and variant ATTR-V30M (V) contains three species of dimers NN, NV, and VV and all three dimers vary by different ligands bound at Cys10-SH.…”
Section: Discussionmentioning
confidence: 98%
“…The most common exogenous source is sulfiting agents used as preservatives in dried fruits and vegetables (2) and in wine where millimolar concentrations have been reported (3). Sulfite is also used as a stabilizer in many drugs administered to patients (4). Interestingly, its presence in a dexamethasone preparation increased the neurotoxicity of excitotoxic agents (5) suggesting that it could have an effect on neuronal cells.…”
mentioning
confidence: 99%
“…Sulfite is one of the few sulfating agents approved by the Food and Drug Administration as a food preservative and antioxidant to prevent or reduce spoilage [3]. It is also used as an ingredient of many medications, such as antibiotics, analgesics, and anesthetics [2,5,6]. It has been suggested that the presence of sulfite in dexamethasone preparations has increased its neurotoxicity of the preparation [73].…”
Section: Discussionmentioning
confidence: 99%
“…Sulfite is used as an antioxidant and preservative in dried fruits, vegetables, pickled onion, and beverages such as fruit juice, grape juice, beer, and wine to prevent or reduce spoilage [2][3][4]. Sulfite is also used as a stabilizer in many drugs and cosmetics [2,5,6]. For the majority of people, exposure to sulfites occurs during consumption of foods and drinks that contain sulfite preservative [2].…”
Section: Introductionmentioning
confidence: 99%